The Development of Pragmatic Competence in EFL Learners - Dilshoda Roxatova (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Pragmatic competence is a key component of effective communication in English as a Foreign Language (EFL). It refers to the ability to use language appropriately according to social and cultural contexts. This thesis examines how pragmatic competence develops in EFL learners and why it is important in modern language education. The study focuses on the role of instruction, cultural awareness, and interaction in developing pragmatic skills. The findings suggest that many learners face difficulties due to limited exposure to authentic communication. Therefore, it is necessary to integrate pragmatic instruction into language teaching to help learners communicate more naturally and effectively.